2021
DOI: 10.5267/j.msl.2020.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Green competitive advantage: Examining the role of environmental consciousness and green intellectual capital

Abstract: The purpose of this study was to examine the role of environmental consciousness and green intellectual capital (GIC) for green competitive advantage. The association between environmental consciousness and each component of GIC—green human capital, green relational capital, green structural capital—is tested in this study. Tests are also carried out to examine the association of each GIC element with green competitive advantage. Data were collected using an online questionnaire. A total of 237 questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 1 publication
3
26
0
Order By: Relevance
“…Regarding the determinants, scholars have argued that companies adopting higher levels of corporate social responsibility would be more conscious to engage themselves in environment management programs. They would take better steps to develop green intellectual capital (Astuti & Datrini, 2021;Chang & Chen, 2012;Sudibyo & Sutanto, 2020). The European Commission conceptualized CSR as an organization's voluntary actions and programs for addressing environmental and social issues as well as maintaining requisite relationships with their stakeholders in this regard (European Commission, 2001).…”
Section: Corporate Social Responsibility Green Intellectual Capital and Green Innovationmentioning
confidence: 99%
“…Regarding the determinants, scholars have argued that companies adopting higher levels of corporate social responsibility would be more conscious to engage themselves in environment management programs. They would take better steps to develop green intellectual capital (Astuti & Datrini, 2021;Chang & Chen, 2012;Sudibyo & Sutanto, 2020). The European Commission conceptualized CSR as an organization's voluntary actions and programs for addressing environmental and social issues as well as maintaining requisite relationships with their stakeholders in this regard (European Commission, 2001).…”
Section: Corporate Social Responsibility Green Intellectual Capital and Green Innovationmentioning
confidence: 99%
“…GCA is a condition under which firms gain sustainable benefits from successful environmental strategies [45]. Astuti and Datrini [17] describe GCA as a situation in which a firm occupies certain positions regarding environmental protection that rivals find difficult to imitate. Hospitality firms that create environmental innovation can gain competitive advantage through a better company environmental image, retention of existing customers and attraction of new customers, increased market share, and improved performance [28,45].…”
Section: Green Competitive Advantage (Gca)mentioning
confidence: 99%
“…There is a lack of clarity on how environmental strategies relate to organisational strategies that lead to competitive advantage. Astuti and Datrini [17] find that environmental innovation mediates the relationship between environmental pressure forces and firm performance in Jordan. Delmas et al [53] investigate the relationship between environmental ethics and firm competitive advantage through the mediating role of GI in manufacturing firms in Taiwan.…”
Section: Mediating Role Of Gi In the Relationship Between(e) And Gcamentioning
confidence: 99%
“…Studies that used a global measure of GIC or that did not distinguish between GIC dimensions in their statistical models (N = 8) found an association between GIC and organizational performance, measured as financial performance [57,69,70], innovation performance [71], or financial, social, and environmental performance [58]. Corporate competitive advantage emerged as an outcome of the adoption of GIC as well [6,57,72,73]. These studies therefore support the view that the greater the effort and investments that firms put in green knowledge, the higher their chances to have a good positioning in the market.…”
Section: Outcomes Of Gic (In Studies With No Distinction Among Dimensions)mentioning
confidence: 99%
“…Among the selected works, only twelve studies identified GIC antecedents. The most mentioned antecedent was environmental consciousness [13,57,73,86], followed by corporate social responsibility (CSR) [13,59,86], GHRM [61,70], corporate environmental ethics [47], strategic intent [71], technological distance [63], and network embeddedness [62]. According to these papers, the association between environmental consciousness and GIC is related to the positive representation of green issues that characterize firms with high levels of environmental consciousness.…”
Section: Antecedents Of Gicmentioning
confidence: 99%